A process-oriented framework for the evaluation of managerial support systems - Rudolf Vetschera; Heinz Walterscheid (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1993)
We propose a new method for evaluating the benefits of decision-oriented information systems. This method is based on a detailed analysis of decision processes. Using prescriptive decision theory, correct results are established for different sub-phases of the process and possible deviations from these results are analyzed. Systems are then evaluated according to their contribution to the elimination of such errors.
Keywords: 330